The determinants of capital structure-An empirical study of Chinese real estate listed companies - Han, Xiao (2017)
This paper researches the determining factors of capital structure of Chinese real estate listed corporations. The panel data set is used to investigate 106 Chinese real estate listed corporations during 2007-2016. Three gearing ratios including total leverage ratio, long-term leverage ratio and short-term leverage ratio are employed separately, and eight explanatory variables are used to test whether they play a role in capital structure, including firm size, growth opportunity, profitability, tangibility, liquidity, state ownership, non-debt tax shields and ownership concentration. A majority of the results are in line with the western capital structure theories and past research. Except ownership concentration, all of variables have an impact on different gearing ratios. Profitability, non-debt tax shields and state ownership are inversely related to leverage, while tangibility plays a positive role in the leverage ratio. Firm size, growth opportunity and liquidity have different signs in different leverage measures. Besides, Chinese real estate listed companies use more short-term debt. Key words: Capital structure, leverage, China, real estate, capital structure theories